The effect of child disability on parents' labour supply : evidence from Colombia (2017)
Evidence from high-income countries has shown that having a child with disabilities (CwD) decreases parents' labour supply. However, little is known about this relationship in lower and middle-income countries. In this paper, we implement a non-linear difference in difference approach to estimate the causal effects of having a CwD on the labour supply of parents in urban Colombia. We use the first two waves (2010-2013) of the Colombian Longitudinal Survey (ELCA) and define treated households as those who did not have a CwD in 2010 but do have one in 2013 and compare them to those who did not have a CwD in any of the two periods. We find that having a CwD increases the probability of working for both parents, but especially for mothers. The effect on the probability of working is similar for single and married mothers. However, for married mothers the probability of working part-time increases while the probability of working full time decreases slightly. In the case of single mothers, the probability of both types of work increases.